False Positive COVID-19 Antibody Test in a Case of Granulomatosis With Polyangiitis - Tzouvelekis, Argyrios; Karampitsakos, Theodoros; Krompa, Anastasia; Markozannes, Evangelos; Bouros, Demosthenes (Frontiers in Medicine, 2020)
Collateral damage due to 2019 novel coronavirus disease (COVID-19) represents an emerging issue. Symptoms of COVID-19 are not disease-specific. Differential diagnosis is challenging and the exclusion of other life-threatening diseases has major caveats. In the era of this pandemic, diagnosis of other life-threatening diseases might delay treatment. The Food and Drug Administration has recently authorized the first antibody-based test for COVID-19; however, RT-PCR of nasopharyngeal or oropharyngeal swabs remains the recommended test for diagnosis. We present the first report of a false positive COVID-19 antibody test in a case of Granulomatosis with Polyangiitis (GPA). Specifically, the case concerns an 82-year-old female, never smoker, who was admitted to our hospital with symptoms of fever and general fatigue that had lasted 7 days. She already had a positive IgM test for COVID-19, yet multiple RT-PCR tests had returned as negative for SARS-CoV-2. In the following days, her renal function deteriorated, while hematuria and proteinuria with active urinary sediment developed. Based on high clinical suspicion for ANCA-associated vasculitis, we performed a complete immunologic profile which revealed positive c-ANCA with elevated titers of anti-PR3. Pulses of methylprednisolone along with cyclophosphamide were applied. At day 10, treatment response was noticed as indicated by respiratory and renal function improvement. This report highlights the need for meticulous patient evaluation in order to avoid misdiagnosis in the era of COVID-19.